Research on the Impact of Voluntary Auditor Changes in Chinese Listed Companies on Audit Fees - Liuting Huang; Shixin Yang (Journal of Frontier in Economic and Management Research, 2025)
This article takes listed companies in China's A-share market that underwent voluntary auditor changes from 2021 to 2024 as the research object, and empirically examines the impact of voluntary auditor changes on corporate audit fees. The research results show that: (1) voluntary auditor changes significantly reduce corporate audit fees, indicating that companies have bargaining advantages in auditor selection and can achieve cost savings by changing auditors; (2) The new regulatory regulations released in 2023 have significantly changed the audit pricing mechanism, so that voluntary changes no longer have a fee reduction effect; (3) When establishing an audit committee for a company, voluntary auditor changes can significantly reduce audit fees; (4) When state-owned enterprises voluntarily change auditors, the cost reduction effect of audit fees is more significant; (5) Voluntary auditor changes have partially mediated the cost reduction effect on audit fees by reducing the proportion of non audit services. This article provides empirical evidence for enterprises to optimize their auditor selection strategies, and also provides insights for regulatory authorities to identify irrational low price competition in the audit market and regulate pricing order.